2021
DOI: 10.3390/microorganisms9122511
|View full text |Cite
|
Sign up to set email alerts
|

Mining the Genome of Bacillus velezensis VB7 (CP047587) for MAMP Genes and Non-Ribosomal Peptide Synthetase Gene Clusters Conferring Antiviral and Antifungal Activity

Abstract: Chemical pesticides have an immense role in curbing the infection of plant viruses and soil-borne pathogens of high valued crops. However, the usage of chemical pesticides also contributes to the development of resistance among pathogens. Hence, attempts were made in this study to identify a suitable bacterial antagonist for managing viral and fungal pathogens infecting crop plants. Based on our earlier investigations, we identified Bacillus amyloliquefaciens VB7 as a potential antagonist for managing Scleroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The genus Bacillus includes several species that are highly similar, and the taxonomic status of Bacillus strains cannot be easily determined using conventional classification methods ( Hamdache et al, 2013 ). Several strains initially identified as B. amyloliquefaciens , including FZB42 ( Schilling et al, 2018 ), vb7 ( Saravanan et al, 2021 ), and SQR9 ( Feng et al, 2018 ), are now classified as B. velezensis . To determine the relationship between TJS119 and other strains of Bacillus , a phylogenetic tree based on 92 core gene sequences was constructed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Bacillus includes several species that are highly similar, and the taxonomic status of Bacillus strains cannot be easily determined using conventional classification methods ( Hamdache et al, 2013 ). Several strains initially identified as B. amyloliquefaciens , including FZB42 ( Schilling et al, 2018 ), vb7 ( Saravanan et al, 2021 ), and SQR9 ( Feng et al, 2018 ), are now classified as B. velezensis . To determine the relationship between TJS119 and other strains of Bacillus , a phylogenetic tree based on 92 core gene sequences was constructed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Using whole-genome sequencing, Zhang et al (2022) found that B. velezensis GS-1 produces the lipopeptides surfactin, fengycin, and plantazolicin, which exhibit inhibitory effects against M. oryzae . Eight secondary metabolite-related gene clusters have been identified in B. velezensis VB7, which is protective against carnation infection by Sclerotinia sclerotiorum , cotton infection by tobacco streak virus, and tomato peanut shoot necrosis infection ( Saravanan et al, 2021 ). Meanwhile, 12 secondary metabolite-related gene clusters have been identified in B. velezensis YC89, which effectively controls red rot disease in sugarcane ( Xie et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…fragariae [76], F. oxysporum f.sp. cubense [77], P. digitatum and P. italicum [78], Sclerotinia sclerotiorum [77], tomato spotted wilt virus, groundnut bud necrosis virus, and tobacco streak virus [77].…”
Section: Discussionmentioning
confidence: 99%
“…citri [ 29 ]. B. amyloliquefaciens VB7 has been shown to be a potential antagonist that can control a number of dangerous diseases ( Sclerotinia sclerotiorum affecting cloves, tobacco stripe virus affecting cotton, and peanut bud necrosis affecting tomatoes) and synthesizes non-ribosomal antimicrobial peptides such as surfactin, butirosin A/butirosin B, fengycin, difficidin, bacillibactin, bacilysin, and mersacidin the Ripp lanthipeptide, as well as a number of other compounds as well [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various mechanisms of phytopathogen suppression by Bacillus strains have been actively studied [ 30 , 31 , 32 , 33 ]. In particular, chitinase and β-1,3-glucanase enzymes produced by B. velezensis CE 100 and the effectively lysing mycelium of Macrophomina phaseolina and Fusarium oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 99%